STUDI PERTUMBUHAN MANGIUM (Acacia mangium Willd) DI AREAL HTI PT. INHUTANI GOWA-MAROS - Rosmarlinasiah Rosmarlinasiah (Universitas Haluoleo, 2018)
ABSTRACTSetting the forest to produce the optimum growth of Acacia mangium Willd is indispensable, in order to provide the optimal forest products and sustainable. To support these efforts need to be made carefully timber estate management plant. The purpose of the research is to find out the condition of the forest growth Mangium and identify factors that influence plant growth conditions are dominant, particularly factors that can be influenced through action management. The research was carried out in the area of PT. Inhutani timber estate Gowa-Maros South Sulawesi on the stands are aged, 1 year, 2 years, 3 years, 5 years, and 7 years. Planting distances vary i.e. 2m x 2m (the stands are aged 1 year), 3m x 3m, and 4m x 2.5m. Research using survey methods, purposive sampling technique in selecting the existing age-class stands at the site of the research. Implementation of research through the data collection of the sample sized area of 0.04 Ha (20m X 20m) with seeking such that the areal example represents the forest growing conditions in the field. Analysis of the growth of Acacia mangium Willd stands using several equations commonly used as model of Richard, model of exponentiation, and model of quadratic. The results showed that the growth of Mangium on site research classified as low. At the age 7 years, Mangium only reaches a height of 13.2 m, diameter 19.9 cm, tallest trees 16.8 m, and basal area 23.9 m2/ha. The value of the highest tree prediction shows that the location of research including bonita 2. The density of Mangium forest belongs to the height indicated by the great crown closure rate achieved 193%. Based on the relationship of the length and diameter of the crown, then it can be said that the crown had inclined mangium conical. Kata Kunci: Growth model, Acacia mangium, management actions.